An electrostatic discharge based needle-to-needle booster for dramatic performance enhancement of triboelectric nanogenerators. (1st December 2018) - Zhai, Cong; Chou, Xiujian; He, Jian; Song, Linlin; Zhang, Zengxing; Wen, Tao; Tian, Zhumei; Chen, Xi; Zhang, Wendong; Niu, Zhichuan; Xue, Chenyang
Graphical abstract: Highlights: A strategy is proposed to improve the performance of triboelectric nanogenerators. The maximum continuous power can be boosted dramatically by electrostatic discharge. This design reduces the optimal impedance that is important for circuit matching. With this design triboelectric nanogenerators can directly drive low-power devices. This work is also significant for macro-energy conversion, such as ocean energy. Abstract: There is plenty of exploitable energy in the ambient environments. Triboelectric nanogenerator is an innovative electricity generation technology to convert the wasted mechanical energy into electrical energy. However, the output of conventional triboelectric nanogenerators cannot be employed efficiently because their tremendous internal resistance limits the current of electrons. Inspired by the principle of lightning rods, for the first time we propose the utilization of electrostatic discharge to improve the performance of triboelectric nanogenerators, which is realized by an opposite needles structure enclosed in an inert atmosphere. When this structure is connected in series with a vertical contact-separation triboelectric nanogenerator, the strong electric field near tips of two needles ionizes the gas around them, forming a conductive plasma channel between the tips, and releasing a mass of free charges. As a result, some exciting performances are obtained in triboelectric nanogenerator. The output peak-to-peak voltage is increased from 300 V to 1300 V, and the equivalent impedance of energy harvesting circuit is reduced from 100 MΩ to 10 kΩ. Especially in the optimal conditions, the maximum continuous power can even be significantly improved by 330.76%. Therefore, this work provides a new strategy for the energy conversion technology, which is significant for the advancement and application of triboelectric nanogenerators.